Bench to Bedside of Neural Stem Cell in Traumatic Brain Injury - Solomon O. Ugoya; Jian Tu (Hindawi Limited, 2012)
Traumatic brain injury (TBI) is one of the leading causes of major disability and death worldwide. Neural stem cells (NSCs) have recently been shown to contribute to the cellular remodelling that occurs following TBI and attention has been drawn to the area of neural stem cell as possible therapy for TBI. The NSCs may play an important role in the treatment of TBI by replacing the damaged cells and eventual remyelination. This paper summarized a critical assessment of recent data and developed a view comprising of six points to possible quality translation of NSCs in TBI.